Digital Archiving of Historical Water Utilization Structures Using an Interdisciplinary Method - MUDIČKA, Štefan; KELLO, Juraj; MATOLÁK, Milan; KAPICA, Roman; SMELÍKOVÁ, Markéta; SMELÍK, Stanislav (GeoScience Engineering, 2021)
Human efforts to regulate watercourses and the use of water energy in their favour goes back into the past. Although historical water management and utilization structures are the proof of that, only a small number of such structures have been preserved. The article deals with the applied research of the use of modern geodetic laser scanning stations in combination with photogrammetric digital technologies for creating technical documentation and digital visualization of historical structures and national cultural monuments. Specifically, in this case, we will focus on the water utilization buildings – the water mill and water sawmill in the National Open-Air Museum, Rožnov pod Radhoštěm, Czech Republic. Digital twins created using modern technologies may well serve not only for geo-tourism purposes but also as basis for potential future reconstruction or redevelopment projects. Keywords: 3D visualization; Digital photogrammetry; Digital twin; Industrial monuments; Laser scanning. DOI 10.35180/gse-2021-0046